Residential colleges as equalizers for sustainable development? Examining impacts on sustainable education and equity across gender and SES - Gui, Pingping; Alam, Gazi Mahabubul; Troise, Ciro; Bresciani, Stefano (John Wiley and Sons, 2025)
Equal access to quality education, both a fundamental human right and an economic cornerstone, has long been enshrined as the United Nations' Fourth Sustainable Development Goal 4 (SDG4). However, disparities in gender and socioeconomic status (SES) hinder its realization. Although residential colleges (RCs) in public universities have proven to be effective, research on RCs in private universities in China is still greatly lacking. Using univariate tests first and then multivariate regression analysis, this study compared RC and non-RC students in public and private universities and found that the fairness of admission to private institutions is poor, but all RCs significantly narrowed the academic gap among students from different social classes, and gender and RC status did not affect grades. Consequently, RCs are effective in reducing academic inequalities in that they give priority to providing equitable educational opportunity for individuals from poorer socioeconomic backgrounds. This is essential for promoting sustainable development in education.